Study of interleukin-6 levels in early diagnosis of neonatal sepsis - Sonawane, Vijay Baburao; Mehkarkar, Nitin S.; Jadhav, Pradnya B.; Gaikwad, Sonali U.; Kadam, Nitin N. (International Journal of Research in Medical Sciences, 2017)
Background:Neonatal septicemia is one of the commonest causes of neonatal mortality and morbidity. Interleukin-6 Levels appears to be one of the most promising candidate cytokine for early diagnosis of neonatal septicaemia. The aim and objectives of this study was to study the role of IL-6 levels as an early marker for diagnosis of neonatal sepsis and to compare IL-6 levels with other septic markers. Methods:This is a hospital based prospective study to evaluate the efficacy of IL-6 as an early diagnostic marker of neonatal sepsis. Eighty neonates, delivered in the hospital, having risk factors for neonatal sepsis, along with those coming to hospital with signs and symptoms of sepsis up to 28 days of life (as study group ) along with normal new-borns admitted to the postnatal ward without high risk factors (control group) were enrolled for this study. Results:IL-6 Levels has shown maximum sensitivity of 95.83%, specificity of 87.50%, positive predictive value of 92%, negative predictive value of 93.33% and accuracy of 92.50 %. E. coli was the most common organism responsible for sepsis. CRP was reported to be highly sensitive (84.21%), and CBC was highly specific (75.00%), IT ratio has sensitivity of 62.5% and specificity of 56.25% while micro-ESR has shown sensitivity of 50.0% and specificity of 62.5%. Out of 80 cases, blood culture (BacTalert) showed growth in 48 cases in study group while two cases in control group. Thus blood culture positivity was 60%. Conclusion:IL-6 test has maximum sensitivity as well as specificity in comparison with other septic markers. Blood culture is the gold standard for the diagnosis of septicemia. CRP is most sensitive while CBC is most specific marker in neonatal sepsis.